Patient Experience Journal Awards: Celebrating our 2019 Recipients - Patient Experience Journal (The Beryl Institute, 2020)
In association with The Beryl Institute, Patient Experience Journal introduced the inaugural Patient Experience Journal (PXJ) Awards. The annual awards celebrate important contributions to the literature and articles of impact in research and practice. They also introduce groundbreaking authors who are working to expand evidence and insights on patient experience and the human experience in healthcare. The winners are selected from the articles published in PXJ and chosen by the Editorial Board of the journal. The award categories are shared and recipients introduced.